A multi-stage-based nonlinear static procedure for estimating seismic demands of steel MRFs equipped with steel slit walls. (15th March 2019) - Ke, Ke; Wang, Fuming; Yam, Michael C.H.; Deng, Lu; He, Yongjun
Highlights: Steel MRFs equipped with steel slit walls may show multi-yielding stages. A multi-stage-based nonlinear static procedure is proposed. The applicability of the current nonlinear static procedure is examined. The proposed method offers a practical tool for modulation of seismic energy balance. Abstract: This paper aims to develop a nonlinear static procedure for estimating seismic demands of steel moment resisting frames (MRFs) equipped with steel slit walls (SSWs) exhibiting multi-yielding stages under seismic actions. The hysteretic behaviour of a steel MRF equipped with SSWs was examined. Numerical models were also developed and verified by revisiting a previous full-scale test programme. The applicability of a classical trilinear kinematic model for idealising the hysteretic response of the systems was examined. Then, a multi-stage-based nonlinear static procedure (MNSP) governed by the energy-balance concept was proposed, which enables practitioners to quantify the seismic demands of a steel MRFs equipped with SSWs showing multi-yielding stages. The MNSP was subsequently applied to two prototype steel MRFs equipped with SSWs under design basis earthquakes and maximum considered earthquakes. The predictions by the MNSP were compared with nonlinear response history analysis (NL-RHA) to examine the effectiveness of the method. The lateral load distributions documented in FEMA-356 were also included in the work for comparison. The observations from this study suggests that the proposed MNSP offers a promising tool for estimating the peak seismic response of steel MRFs equipped with SSWs showing multi-yielding stages.